Genetically Determined Platelet Count and Risk of Cardiovascular Disease: Mendelian Randomization Study. Issue 12 (December 2018) - Gill, Dipender; Monori, Grace; Georgakis, Marios K.; Tzoulaki, Ioanna; Laffan, Mike
Abstract : Objective—: Cardiovascular disease, including coronary artery disease (CAD) and ischemic stroke, is the leading cause of death worldwide. This Mendelian randomization study uses genetic variants as instruments to investigate whether there is a causal effect of genetically determined platelet count on CAD and ischemic stroke risk. Approach and Results—: A genome-wide association study of 166 066 subjects was used to identify instruments and genetic association estimates for platelet count. Genetic association estimates for CAD and ischemic stroke were obtained from genome-wide association studies, including 60 801 CAD cases and 123 504 controls, and 60 341 ischemic stroke cases and 454 450 controls, respectively. The inverse-variance weighted meta-analysis of ratio method Mendelian randomization estimates was the main method used to obtain estimates for the causal effect of genetically determined platelet count on risk of cardiovascular outcomes. We found no significant Mendelian randomization effect of genetically determined platelet count on risk of CAD (odds ratio of CAD per SD unit increase in genetically determined platelet count, 1.01; 95% CI, 0.98–1.04; P =0.60). However, higher genetically determined platelet count was causally associated with an increased risk of ischemic stroke (odds ratio, 1.07; 95% CI, 1.04–1.11; P <1×10 −5 ), including all major ischemic stroke subtypes. Similar results were obtained in sensitivity analyses more robust to the inclusion of pleiotropic genetic variants. Conclusions—: This Mendelian randomization study found evidence that higher genetically determined platelet count is causally associated with higher risk of ischemic stroke. Abstract : Supplemental Digital Content is available in the text.